Semen Sexing in Bovine: Current Status and the Need to Develop Alternative Techniques - Joshi, Himani; Mathur, Manya; Mohanty, AK; Kumar, Sudarshan; Kaushik, JK; Mohanty, TK; Kumar, Dharmendra; Singh, Sumit Kumar; Bhushan, Vanya; Parashar, Abhishek; Bhardwaj, Preeti; Yata, Vinod Kumar (Animal Reproduction Update, 2021)
Livestock industry is one of the important pillars for country economy. Sperm sexing has the potential of significantly improving the quality and quantity of production in the livestock industries. Over years several attempts, involving several different parameters of sperm cells, have been made to develop an efficient sperm sorting procedure. Till date, the only commercially available method for bovine sperm is flow cytometry. The disadvantages associated with this approach, however, points towards the need for developing a more non-invasive and cost efficient approach for separation of X and Y chromosome bearing spermatozoa. In this review paper, we attempt to highlight all the previously developed approaches, as well as other emerging immunological and proteomics based methods that might have the potential of being developed as a promising breakthrough approach for semen sexing. Furthermore, we discuss the advantages and applications of semen sexing in India and around the world.